2009
DOI: 10.1007/s00467-009-1346-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of angiotensin II receptor type 1 antagonists in children and adolescents

Abstract: Our purpose was to evaluate the effects of angiotensin II receptor type 1 antagonists (ARAs) in children and adolescents with hypertension or/and several kinds of nephropathies on blood pressure (BP) and proteinuria and to evaluate related safety issues. Data sources were Medline, Embase, The Cochrane Library, BIOSIS Previews, contact with investigators and manufacturers, personal bibliography of the lead author, and manual searches. We selected randomized controlled trials (RCTs), uncontrolled trials, and cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
(124 reference statements)
2
10
0
Order By: Relevance
“…As reported by other authors [40], enalapril and losartan were well tolerated, similar to the experience reported in hypertensive otherwise healthy preschool and school children [41].…”
Section: Discussionsupporting
confidence: 88%
“…As reported by other authors [40], enalapril and losartan were well tolerated, similar to the experience reported in hypertensive otherwise healthy preschool and school children [41].…”
Section: Discussionsupporting
confidence: 88%
“…Similar congenital malformations seen with ACEI exposure during pregnancy have been reported 32. Studies involving candesartan, losartan, and valsartan showed no effect on growth during study periods of 52 weeks for each 32,34…”
Section: Clinical Studies Safety and Efficacysupporting
confidence: 67%
“…Losartan reduced DBP in a dose dependent fashion at doses from 0.75 mg/kg/day to 1.44 mg/kg/day and was well tolerated. A small irbesartan study indicated that doses of 75–150 mg/day were efficacious in the treatment of hypertension but a later study in children ages 6–16 years failed to show a significant antihypertensive effect 5,12,32. In the Assessment of Efficacy and Safety of Olmesartan in Pediatric Hypertension (AESOP) study, two groups of children ages 6–16 years of age were enrolled and given either low-dose (2.5–5 mg) or high dose (20–40 mg) Olmesartan daily for three weeks.…”
Section: Clinical Studies Safety and Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…They are also recommended for children 14. These drugs are generally felt to have very favourable side-effect profiles in adults1 and children 3. Some authors have even stated that the side effects are similar to those of placebo 5…”
Section: Introductionmentioning
confidence: 99%